EVALUATING THE EFFECTIVENESS OF PORPE METHOD IN ENHANCING READING COMPREHENSION: A STUDY OF SELF_ESTEEM AS A MODERATING FAKTOR - Sari, Rahma Kamanda; Zaim, M (English Review: Journal of English Education, 2024)
This study explores the effect of using PORPE method and students’ self-esteem toward reading comprehension achievement. The objectives of the research are to find out whether: (1)PORPE method produces higher achievement in reading comprehension on junior high schools students; (2) There is an interaction between PORPE method and students’ self-esteem toward students’ reading comprehension. The study categorized as an experimental research. The population of the research was the eighth grade students in the academic years 2023/2024. The sample of this research was taken by using cluster random sampling. The sample was 54 students with 27 students of experimental class taught by using PORPE method and 27 students of control class taught using conventional method by teacher. The data collection was done by giving self-esteem questionnaire and reading comprehension test (pre and post test) after five meetings of treatments.  The data analysis was done by applying T-test and Two ways ANOVA to test the hypothesis. The findings of this research are (1) The use of PORPE method produces higher achievement in reading comprehension on junior high school students; (2) There is no interaction between PORPE method and students’ self-esteem toward students’ reading comprehension.